Characterizing flotation processes of Platreef PGM ores: The applicability of models based on the Weibull and γ rate constant distributions - Ngema, Sithandokuhle Fortune (University of the Witwatersrand, Johannesburg, 2024)
This dissertation delves into a comprehensive examination of the flotation behaviour of Platreef Platinum Group Metal ores, with a specific focus on the applicability of two widely used distribution models, the Weibull and Gamma distributions. The primary objective of this study was to demonstrate the effectiveness of these models in characterizing the flotation response of the ore under varying grind sizes, ranging from 80% passing 150 μm down to 38 μm, and under varying collector dosages. In this research, a series of meticulous experiments that involved the collection of samples from Platreef PGM ore were conducted. These samples were characterized based on their mineralogical composition, and their flotation behaviour across specified particle size distributions and varying collector dosages. The gathered data were then subjected to analysis using the Weibull and Gamma models. This allowed the assessment of the flotation performance of the ore and the description of the intricate flotation sub-processes involved to be possible. The parameters for both the Weibull and Gamma distributions were determined through a rigorous statistical method known as regression. This method involved fitting the experimental data to the models and iteratively adjusting the model parameters until convergence to their most accurate estimates was achieved. The results from the research reveal that both the Weibull and Gamma models demonstrate a commendable ability to describe the flotation process of Platreef PGM ores. However, the study also highlights certain limitations of these models, especially when dealing with coarser grind sizes, where the Weibull model shows a slight decrease in effectiveness. The investigation also points to the significant impact of liberation and grinding time on the accuracy of these models. These findings underscore the importance of understanding the nuances of particle interactions and liberation at different grind sizes in floatation processes. Furthermore, the effect of varying collector dosages on the performance of the models was explored. It was observed that the accuracy of the models diminishes with longer residence times, particularly when collector dosages are changed. This sensitivity to longer residence times and grind characteristics underscores the need for a holistic approach to model development. Another intriguing aspect of the study was the relationship between collector dosage and grind characteristics. It became apparent that increasing collector dosage has a more v pronounced positive effect on recoveries for both coarser and finer grinds, while the intermediate grinds exhibit a less substantial improvement. This discovery challenges the convention of a near-linear relationship between collector dosage and recovery. In conclusion, the research provides valuable insights into the complexities of the flotation process for Platreef PGM ores and underscores the significance of selecting the most appropriate distribution models based on specific ore characteristics and grind sizes. The dissertation also highlights the need for a nuanced approach to process optimization, acknowledging the interplay of factors such as liberation, grind characteristics, and collector dosage. This understanding can be applied to enhance recovery rates and efficiency in flotation processes, offering valuable contributions to the field of mineral processing and chemical engineering. Findings of this work shed light on the intricate nature of chemical processes, emphasizing the importance of a holistic approach to model development and practical applications.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Flotation; rate distributions; Gamma; Weibull; SDG-7: Affordable and clean energy